2011
DOI: 10.1002/ptr.3249
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention with Aqueous Extract of Butea monosperma flowers results in normalization of nuclear morphometry and inhibition of a proliferation marker in liver tumors

Abstract: Butea monosperma (Lam.) (family: Fabaceae) popularly known as 'Palas' or 'fire of forest' has been used traditionally as a hepatoprotective agent. This study evaluated the hepatoprotective and antitumorigenic properties of the aqueous extract and butanol fractions of B. monosperma flowers in animal models. Dried flowers of B. monosperma were extracted with water and fractionated further using n-butanol. The hepatoprotective activity of the aqueous extract was initially confirmed in a carbon tetrachloride-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…More recently, we reported the over‐expression of the RPS27a gene in an oncomouse model of hepatocellular carcinoma . The RPS27a levels decreased sharply following a chemopreventive intervention . Despite the emerging significance of RP genes in cancer development, cell cycle and cellular senescence, little is known about their regulatory control mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we reported the over‐expression of the RPS27a gene in an oncomouse model of hepatocellular carcinoma . The RPS27a levels decreased sharply following a chemopreventive intervention . Despite the emerging significance of RP genes in cancer development, cell cycle and cellular senescence, little is known about their regulatory control mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This can be extrapolated from the fact that rapidly dividing hepatocytes in HCC tissue may have a higher metabolic rate than normal liver cells, and persistently high levels of RPS27a could contribute towards enhanced ribosome synthesis and protein turnover. Moreover, treatment of X15-myc mice with a plant extract bearing anti-cancer properties abolished the expression of RPS27a; these studies not only emphasized the involvement RPS27a in hepatocarcinogenesis, but also indicated a putative prognostic value of this protein (Mathan et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…Subsequent studies suggested that some ribosomal proteins are overexpressed in HBV-associated human HCC tissues (Kim, 2006;Kim et al, 2004;Mathan et al, 2011). Enforced expression of ribosomal protein L36a is associated with increased cell proliferation and colony formation due to rapid cell cycling (Kim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aqueous extract of Butea monosperma (Lam.) flower could reduce VEGF generation and inhibit proliferation of liver tumors of rats (Mathan et al, 2011). Resveratrol is a polyphenol, which could be found in grapes, various berries, peanuts, and many plant sources; it could suppress the proliferation for human ovarian and osteosarcoma cancer cells through inducing HIF-1ɑ degradation and downregulating VEGF expression (Cao, Fang, Xia, Shi, & Jiang, 2004).…”
Section: Discussionmentioning
confidence: 99%